Motor Preparation of Step Initiation: Error-related Cortical Oscillations. (21st November 2018) - Delval, Arnaud; Braquet, Aurore; Dirhoussi, Nauaman; Bayot, Madli; Derambure, Philippe; Defebvre, Luc; Tard, Céline; Dujardin, Kathy
Highlights: Attention disrupts movement preparation and leads to errors in motor programming. Errors are associated with a prolonged beta power decrease over the sensorimotor cortex. Alpha/beta oscillations are sensitive markers of non-conscious motor error monitoring. Abstract: Gait initiation can vary as a function of the available and engaged attentional resources. Conflict resolution can disrupt movement preparation and lead to "errors" in motor programming. These "errors" are physiologically useful by enabling us to adapt our motor behavior to situations with conflicting information. The objective of the present study was to analyze the patterns of cortical activation associated with motor programming errors and the corresponding error corrections. Incongruent flankers around a target arrow were used to trigger errors in anticipatory postural adjustments (APAs) prior to gait initiation; i.e. perturbed motor programming but normal execution. Thirty healthy adults performed a gait initiation task. The event-related potentials (ERPs) and event-related desynchronization (ERD) after target presentation were analyzed according to the presence or absence of an APA error. The ERP was similar in both conditions, except that the Ne and P300 peak latencies were longer for APA errors. Motor programming errors during gait initiation were characterized by longer, less intense low-beta-band ERD over the sensorimotor cortex and alpha ERS followed by stronger alpha ERD during errors. APA errors were associated with a specific alpha/beta oscillation profile over the sensorimotor cortex; these beta oscillations might be sensitive markers of non-conscious motor error and correction monitoring.